Mejores colegios en Colombia: efecto de las condiciones socioeconómicas sobre el desempeño escolar (2021)
This paper presents evidence on the effects of using socioeconomic status (SES) adjusted test scores on schools ranking. Adjusted scores are estimated from the residuals of a linear regression model using data from the Saber 11 exam for the 2014-2020 period. I found that the use of SES-adjusted test scores reduces the socioeconomic gap between schools ranking in the highest performance decile and those ranking below by 69%. This result emphasizes the importance of calculating measures that differentiate the effect of variables that are beyond school control. This paper also presents a data visualization tool that includes indicators on the relative performance of schools, the distribution of their students, and their progress over time based on both adjusted and unadjusted scores. Ultimately, this tool will allow all stakeholders to make decisions based on a broader and more accurate picture of educational quality.